The Concentration Variation Effect of Earring Leaves (Acalypha Indica L.) Extract on It’s Bioactivity Ability in Inhibiting The Growth of Salmonella Typhi (S. Typhi) - Ziana, Elma; Furqan, Repika Nurul; Nurul Furqan, Baiq Repika (Biota, 2022)
The research has been carried out on the effect of variations in the concentration of earring leaves (Acalypha Indica L.) ethanol extract on the acquisition of inhibition zone values for the growth of S. typhi bacteria. In this study, ethanol solvent was used in the maceration and evaporation stages, then the well diffusion method was used to test its antibacterial activity. Each stage was carried out in triplo and 3 repetitions. Phytochemical test on the evaporated extract showed positive test results for flavonoid and tannin metabolite compounds. Concentration variations that used in this study were 5%, 15%, 30%, 50% and 60%, the antibiotic chloramphenicol was also used as a positive control and aquadest as a negative control. Meanwhile, the antibacterial activity test gave the result that the higher the concentration of the earring leaf extract (Acalypha Indica L.), the inhibition zone value also increased with the following successive values: 0mm, 11mm, 14mm, 15mm and 16mm, on the other hand chloramphenicol showed an inhibition zone of 32 mm. The research data were analyzed statistically using the One Way Anova test. Earring leaf extract (Acalypha Indica L.) has a significant effect of 0.000 on S. Typhi bacteria. However, at the smallest concentration, namely 5%, it does not have an inhibition zone diameter of 0 mm with a significant value of 1000. It can be concluded that the antibacterial activity using chloramphenicol is still higher when compared to the antibacterial activity using the ethanol extract of earring leaves (Acalypha Indica L.) in inhibiting growth of S. Typhi bacteria.